Proposed new interior design of Art Center at Lot A,B & C, Block P2, Lorong Selangor, Gaya @ Melawati Urban 2, Taman Melawati, 53100, Gombak, Selangor For Mouth & Foot Painting Artist Centre Sdn. Bhd. / Jamilah Jamal - Jamal, Jamilah (Faculty of Architecture, Planning and Surveying, 2012)
Project report is compulsory and it is an assignment that needs to be carried out by all final year students. Final year student of Diploma in Interior Design are required to write detail about Interior Design Final Project. Besides that, project report aims to provide explanation on project handled for Interior Design final project. Student must clearly understand the project they are doing so that the project will run smoothly and successful. This project title is Proposed New Interior Design of Art Center at Lot A, B &C, Block P2, Lorang Selangor, Gaya @ Melawati Urban 2, Taman Melawati, 53100, Gombak, Selangor For Mouth And Foot Painting Artist Sdn. Bhd Taman Melawati . The aim of design is to design a new art center for mouth and foot painting artist, staffs and visitor with new image at the same time remain the corporate identity. The objective of this project actually is to create more spacious and functional space for easy access to the Mouth And Foot Painting office which consider the requirement for each end user and every disabled person especially for those who are using wheelchair.